Gut Microbiota Composition and Predicted Microbial Metabolic Pathways of Obesity Prone and Obesity Resistant Outbred Sprague-Dawley CD Rats May Account for Differences in Their Phenotype - Obanda, Diana N.; Keenan, Michael J.; Page, Ryan; Raggio, Anne M.; Taylor, Christopher M.; Marx, Brian D.; Stout, Rhett W.; Guice, Justin; Luo, Meng; Welsh, David A.; Coulon, Diana; Husseneder, Claudia (Frontiers in Nutrition, 2021)
Like humans, outbred Sprague-Dawley CD rats exhibit a polygenic pattern of inheritance of the obese phenotype and not all individuals exposed to a high calorie intake develop obesity. We hypothesized that gut microbiota composition accounts for phenotype differences between obese prone (OP) and obese resistant (OR) rats. We studied the gut microbiota composition and predicted microbiota function of OP and OR rats after a high fat (HF) diet and how they respond to fermentation of resistant starch (RS). In phase 1, OP and OR rats were fed a HF diet. To determine causal role of microbiota on phenotype, in phase 2, a microbiota transplant between the phenotypes was performed before switching all rats to a HF diet supplemented with 20% RS. Despite a similar calorie intake, OP rats gained more weight and accumulated more abdominal fat in both phase 1 and 2 compared to OR rats (P<0.001; n=6). The OP rats fermented RS more robustly compared with OR rats with an increase in total bacteria, short chain fatty acids, and increased weight of the cecum, but microbiota of OP rats had much lower alpha diversity and evenness. The microbiota of OP rats had higher amounts of bacteria from order Bacteroidales, specifically family Muribaculaceae (S24-7), which is known to possess several starch degrading enzymes and was reported in previous studies to increase with fermentation of RS. The OR rats fermented RS less but had higher bacterial diversity and evenness and had significantly higher bacterial counts from phylum Firmicutes particularly order Clostridiales, genus Clostridium and an uncultured bacterium of the genus Akkermansia. The microbiota of OR rats had enhanced bacterial chemotaxis, phosphotransferase system (PTS), and fatty acid biosynthesis compared to OP rats whose microbiota had higher glycan degradation and LPS biosynthesis pathways. The microbiota transplant did not change obesity phenotype or microbiota composition. In conclusion, a higher alpha-diversity and evenness of the microbiota and higher proportions of Clostridiales and Akkermansia in OR rats were associated with a better metabolic phenotype with lower body fat. However, robust RS fermentation caused a lower diversity and evenness and did not result in a leaner phenotype.